2005
DOI: 10.1185/030079905x38150
|View full text |Cite
|
Sign up to set email alerts
|

Closing the osteoporosis management gap in primary care: a secondary prevention of fracture programme

Abstract: A simple scan identified patients with prior fracture and with osteoporosis. Prior fracture was confirmed to be a strong predictor of osteoporosis; 86.4% of women with a fracture history had low BMD and 51.9% had osteoporosis. Similar disease management programmes elsewhere in primary care to identify high risk patients and ensure appropriate prescribing would, in addition to implementing national guidelines, be pharmaco-economically prudent and improve management of patients with fragility fracture across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 21 publications
2
13
0
1
Order By: Relevance
“…Compared to usual care in the UK, for every 1,000 fragility fracture patients assessed by the FLS, 18 fractures (including 11 hip fractures) will be prevented, with net cost-saving of £21,000 (€23,350, US$ 34,700) after taking into account all costs including costs of treatments [84]. In the UK, the Department of Health accepted the following arguments: based on the evidence (1) that half of hip fracture patients have suffered prior fractures [14][15][16][17] and (2) 16% of post-menopausal women have sustained a fracture [11][12][13], it follows that a FLS provides an opportunity for early intervention for half of all potential future cases of hip fracture by targeting only one sixth of the post-menopausal population. Cost savings from national implementation of FLS, potentially amount to £8.5 million over 5 years.…”
Section: Cost-effectiveness Of Coordinator-based Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to usual care in the UK, for every 1,000 fragility fracture patients assessed by the FLS, 18 fractures (including 11 hip fractures) will be prevented, with net cost-saving of £21,000 (€23,350, US$ 34,700) after taking into account all costs including costs of treatments [84]. In the UK, the Department of Health accepted the following arguments: based on the evidence (1) that half of hip fracture patients have suffered prior fractures [14][15][16][17] and (2) 16% of post-menopausal women have sustained a fracture [11][12][13], it follows that a FLS provides an opportunity for early intervention for half of all potential future cases of hip fracture by targeting only one sixth of the post-menopausal population. Cost savings from national implementation of FLS, potentially amount to £8.5 million over 5 years.…”
Section: Cost-effectiveness Of Coordinator-based Systemsmentioning
confidence: 99%
“…Since 16% of patients [11][12][13] who have sustained a fragility fracture over the age of 50 ultimately yield 45% of hip fracture cases [14][15][16][17], targeting of osteoporosis services to them is highly cost-effective. Yet, recent reviews have demonstrated large unmet needs in the management of these patients: despite the evidence, few patients with fragility fractures receive osteoporosis investigation or treatment [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies from Australia [11], UK [12], and USA [13] have confirmed these findings for current hip fracture sufferers. Figure 2 attempts to make these data accessible to generalists in the healthcare system, be they primary care providers or those who commission acute-and long-term services in the NHS [8,14]. This figure shows, for example, that we can divide the entire postmenopausal population into those women who have a fracture history (above the dotted line) and those women who have yet to suffer a fracture (below the line).…”
Section: Fracture Case Findingmentioning
confidence: 99%
“…If a doctor or allied healthcare professional can ask the question, "Have you experienced a fracture Madam?" and a patient can remember (and studies have indicated that they generally do [16][17][18]), this provides a simple case finding strategy to identify fragility fracture patients that may not have received osteoporosis assessment at the time their prior fracture occurred [8,14]. Fig.…”
Section: Fracture Case Findingmentioning
confidence: 99%
“…[23][24][25] However, ambulatory programs may miss women in poor health. Women invited to, but not attending, a screening intervention, were older, had poorer health and a higher number of falls.…”
mentioning
confidence: 99%